Survival Enterohaemorrhagic E.coli O157in locally produce soft cheese in Baghdad city and studying the effect of some physical factors on its viability: Najim Hadi Najim , Zina saab khudhier And Ahmed Hadi Mohammed - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2008)
A total of 24 samples of three different kinds of locally produced softcheese manufactured from raw milk of Cows , Buffaloes and Ewes( 8 samples of each) were collected at weekly intervals from differentareas of Baghdad city in the period from the beginning of December2007 till the end of January 2008.The main objective of this study was to isolats , identify andenumerate Enterohaemorrhagic E.coli O157from locally produced softcheese , besides that , to study the effect of cheese storage temperature(4 C) and different salt concentration solutions on the viability andsurvival of E.coli O157 in stored cheese .Data demonstrate that 11 out 24 of samples 45.84% were found tohave Enterohaemorrhagic E.coli O157 and their average counts were1.6× 104 CFU/gm.The result of statistical analysis demonstrate that cheese samplesmanufactured from cows raw milk had significantly ( P> 0.05) higherE.coli O157 counts and isolation rates over both cheese samples thatwere manufactured from Ewes and buffaloes raw milk .the average count of Enterohaemorrhagic E.coli O157 in cheesemanufactured from cows milk were 3.8× 104 CFU/gm and the isolationpercentage was 75% while their average counts in cheese manufacturedfrom Ewes and buffaloes milk were 7.3 ×103 & 2.4 ×103 CFU/gmrespectively and the isolation percentages were 37.5 % & 12.5%respectively.Data revealed that all soft cheese samples that were found to haveEnterohaemorrhagic E.coli O157 and stored at refrigeration temperature(4 C) had non significant ( P<0.05) reduction in the average counts ofE.coli O157after 3 weeks of storage and this indicate that the refrigerationstorage temperature (4 C) had no significant effect on the viabilityand survival of E.col O157 .All soft cheese samples that were found tohave Enterohaemorrhagic E.coli O157 were stored in brinesolutions at different salt concentrations such as 2.5%, 5%,7% and10% for 24 hr,1 week, 2weeks & 3weeks . Data revealed that brinesolution at high concentration of salt such as 10% had nonsignificant effect on the viability and survival of E.coli O157after 3weeks of storage.